SPE Western Regional Meeting 2012
DOI: 10.2118/153894-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance of Multiply Fractured Horizontal Wells

Abstract: The objective of this study was to conduct a modeling study to determine the production performance of multiply fractured horizontal well completed in Shale formations and to investigate the impact of hydraulic fractures on the production performance of horizontal wells in ultra-low permeability formations. A commercial reservoir simulator was utilized to model both single and a dual porosity reservoir since both hydraulic fractures and natural fractures play significant roles in well performance of the low pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As a result, the characteristics of the reservoir interior (stimulated reservoir volume) have a significant impact on production during this early period. These characteristics include the number; the location, and the half-length of hydraulic fractures (Belyadi A. et al 2012). Furthermore, the production profiles, after 5 years, for 7 and 13 stages in 4000×2000 ft 2 case are almost parallel.…”
Section: Production Decline Behavior Analysismentioning
confidence: 85%
See 2 more Smart Citations
“…As a result, the characteristics of the reservoir interior (stimulated reservoir volume) have a significant impact on production during this early period. These characteristics include the number; the location, and the half-length of hydraulic fractures (Belyadi A. et al 2012). Furthermore, the production profiles, after 5 years, for 7 and 13 stages in 4000×2000 ft 2 case are almost parallel.…”
Section: Production Decline Behavior Analysismentioning
confidence: 85%
“…Our previous investigations (Belyadi A. et al 2012) indicated that two periods production are present in a horizontal well with multiple hydraulic frac stages. During the early period the interior of the reservoir (also referred to as the stimulated reservoir volume) contributes most of the production.…”
Section: Base Model Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…These characteristics include the number; the location, and the half-length of hydraulic fractures (Belyadi, A. et al 2012). This suggests that during this period the production is primarily originates from the interior of the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous investigations (Belyadi, A. et al 2010, Belyadi, H. 2011, and Belyadi, A. et al 2012, a multi-layer, dual porosity model with adsorbed gas was employed as the base model for the simulation runs. A commercial reservoir simulator was used to model a horizontal well with multiple hydraulic fractures in the base model.…”
Section: Base Model Developmentmentioning
confidence: 99%